Kawasaki Disease in Infants in the First 3 Months of Age in a Mexican Population: A Cautionary Tale - Garrido-García, Luis Martín; Gutiérrez-Alanis, Juan Humberto; Ramírez-Perea, Ana Isabel; Tremoulet, Adriana; Yamazaki-Nakashimada, Marco Antonio (Frontiers in Pediatrics, 2020)
Abstract Background. Kawasaki disease (KD) is an acute febrile illness that largely affects young children before 5 years of age. Younger children with KD are reported to have a higher prevalence of coronary artery abnormalities. Little is known about infants in the first three months of age diagnosed with KD. Methods. A retrospective study was conducted at the National Institute of Pediatrics in Mexico City form 1995 to 2019. Clinical features, laboratory results and cardiac outcomes were recorded. Infants in the first 3 months of age were compared with older patients. Wilcoxon-Mann-Whitney analysis was performed for continuous variables and Fisher’s exact test for categorical variables. Results. 688 cases of KD were included in this study. Fourteen cases were diagnosed in the first three months of age. Heart failure and KD shock-syndrome was found in 5 cases (35.7%). Giant coronary artery aneurysms were found in 6 cases in the younger group (42.9%). Conclusions. Diagnosis of KD in children younger than 3 months of age is rare. In most cases, an incomplete presentation contributed to a delay diagnosis, treatment and complications. Younger patients with KD have an increased risk of presenting cardiac complications, including giant coronary artery aneurysms, shock and death.